Genetic parameters and polymorphism in candidate genes for growth and conformation traits in boer goats - Javanmard, Arash (2012)
T'he Boer goat, one of the most popular meat iype breed in the world, has many remarkable characteristics such as a fast growing rate, good carcass quality and excellent body conformation. Malaysia has irnported large numbers of Boel goats to develop goat farming in the country. In this respect, it is important to ídentify factors influencing the growth and lept'oductive performance of the Boer goat in order to design optirnal bleeding and selection programs. The objective of this study was to evaluate the growth and reproductive performance of Boer goats using quantitative and molecular approaches. Three independent studies were carried out. In the first study, kid gl.owth an<l doe reploductive performance were evaluated based on non-genetic factors including the year of bilth, sex of the kid, litter type, parity and their interactions, and genetic factors which were relatcd to growth, reproductive and body confolmation traits. Data fol this study were obtained fi'orn a commercial farm (iVision Bio Farm) in Janda Baik, Pahang. The project began in 2006 wlth 397 purebled Boer offsprings born in Malaysia and "174 does and 1.6 bucks as a base population imported from Australia. The research and data collection from the farm continued until 2010, duling which the pcdigree information on 1000 goats was obtained. Heritability estimates for growth and performance traits were detelmined using several different univariate and rnultivariate animal models with the derivativefree approach of restlicted rnaximurn likelihood algorithrn. The average weight at birtll weaning (3 months) and at 6 months of age was 3."12!0.77 kg, 1,0.98x2.99 kg and 21.98t0.30 kg, respectively. T'he average daily gain for different periods, namely flom 0-3, 3-6 and 0-6 months of age were 87.91+33.2 g, 1.04.62x47.1.5 g and 108.32+18.3 g, respectively. The avel.age littel size was 7.64+0.67 per birth. The average body length, height at withers, heart girth and chest depth at weaning were 43.5+5.84 cm, 44.3t1,2.00 cn,47.24+6.32 cm, and 20.8=237 cm, respectively. The values of the same body conformation traits at six months of age wcre 59.1!7.45 cn¡ 56.6+5.46 cm, 58.7+6.08 cm, and 22.49x2.89 cm, respectively. Dir.ect heritabilities (hr) in single ir.ait analyses were 0.29+0.09, 0.27+0.00, an<l 0.69!0.07 weights at birth, weaning and 6 months, lespectively and 0.0510.00, 0.8310.02, and 0.57+0.08, for average daily gain from birth to three months, three to six months of age and frorn birth to six months of age, respectively. The effects of the year of birth, sex of kid and litter'type wel'e significant (p<0.01) for rnost of the measured growth traits. Helitability estimates for most of the performancc traits revealed a moderate level of genctic valiability in these tlaits. In the second study, an investigation was carlied out to determine the polymorphism in eight candidate genes in Boer does. The investigated genes were calpastatiry insulin-like growth factor binding protein 3,kappa-casein, leptin, myostatin, pituitary-specific transcription factor, stearoyl-CoA desaturase, and s-casein. Polymerase chain reaction restriction fragment length polymorphisrn (PCR-RFLP) assays were used to genotype these candidate genes in each animal. The obselved allele size at the 12 loci investigated was similar to tl-rat repolted in the literature. Overall, mosi of ihe genes showed polymorphism except for the IGFBP3 and kappa-casein genes. The Boer goats showed a high frequency of allele B for calpastatin (0.5a), allele T for leptinl (0.55), allele A for leptin2 (0.85), allele T for leptinS (0.65), and allele T fol POUF1 In the third siudy, a partial genorne scan was carried out to identify tire quaniitaiive trait loci (QTL) controlling per.forrnance and body conformation. To map the QTL for live body weight, growth and body conforrnation tr aits in a pur.ebr.ed Boer goat population, multiple eTL aualyses using 45 rnicrosatellite mar.ke r.s spanning 605 centirnorgan on clr¡ornosome 1,2,5,6 and 26 were conducted. Data wer.e analyz_ed using the half sib experimcntal design and the online eTL Express p1.ogr.âm. Two QTLs associated with birth weight were identified, which were located between markers BMC1009 and RM029 in chromosome S. and near marker INRABEN1T2 on chrornosome 26 (p<0.01). Other chromosomal regions did not show any eTL on the growth trait. Two QTLs for the body conformaiion traits wele located only in chromosome 1 and 26. In conclusion, it is clea¡ that there is an additive genetic variation in Boer goats in Malaysia. Mediurn to high her.itability estimates for early growth traits observed may be considered when designing an effective progl.am to irnplove growth char.acter istics. The magnitude of the heritability esiimates for weaning and post weaning weights indicated that those traits would r.espond to mass selection. However; the low heritability of litter size was caused by not only a low genetic variance but also by other. Iaudom or unidentified environrnental factors. Theleforc, the improvement of these traits is likely to be achieved through crossbreeding or improved feeding and rnanagement practices. The adequate genetic variation makes it possible to impr.ove the Boer goat productivity in Malaysia. In ihis study, the Boer. goat also showed a medium level of polymorphism in the candidate genes investigatcd. However, an evaluation of the phenotypic recor.ds for. growth, meat quality and test of the association between alleles/genotypes and the traits have to be carried out before any allele at these loci may be considered as a favorable allele in selection programs for the Boer goats. Identifying genes affecting QTL of growth are imporiant and has the potential to significantly increase the rate of genetic improvement through the use of marker-assisted selection. The results of the candidate genes and QTL analyses in this study will serve as reference for future studies on QTL mapping to cnhance goat productivity.